Manipulação experimental da colonização de detritos foliares por invertebrados aquáticos em um riacho tropical de 3ª ordem - Uieda, V. S. [UNESP]; Carvalho, E. M. (FapUNIFESP (SciELO), 2015)
Through a manipulative experiment, the colonization of leaf litter by invertebrates was investigated in two sections of a tropical stream (spatial scale) that differed in function of the canopy cover, one with the presence (closed area) and another without riparian vegetation (open area), during one month of the dry and one of the wet season (temporal scale). The work aimed to verify differences related to four variables: season, canopy cover, leaf type and leaf condition. Litter bags containing arboreal and herbaceous leaves (leaf type variable), non-conditioned and preconditioned (leaf condition variable) were placed at the bottom of the stream in each area (canopy cover variable) and season (dry and wet), and removed after 13-day colonization. The analysis of the remaining litter dry mass per leaf bag emphasizes differences related mainly to seasonality, canopy cover and leaf type, although leaf condition was also important when combined with those three factors. Comparing the abundance of invertebrates per treatment, there was a tendency of high predominance of Chironomidae during the dry season and greater taxa diversity and evenness during the wet season, when the water flow increase could alter the availability of microhabitats for local fauna. Even though canopy cover alone was not a significant source of variation in the abundance of invertebrates, the results showed a tendency of a combined effect of canopy cover with seasonality and leaf condition.
Experimental manipulation of leaf litter colonization by aquatic invertebrates in a third order tropical stream
Keywords: Aquatic insects; Headwater streams; Leaf breakdown; Seasonal variation; Spatial variation